Geschichte der Krim: Iphigenie und Putin auf Tauris - jobst, kerstin s. (2020)
The book surveys the history of the Crimea from ancient times to the present, reflecting both the latest research and the author's own recent findings. In the context of recent developments in the Crimea and what most legal experts regard as Russia's illegal annexation of the Crimean Peninsula, the study examines the historical background for today's conflict.